Principles and practice of anesthesia for thoracic surgery - Slinger, Peter; SpringerLink (Online service). (New York Springer, 2011)
Principles and Practice of Anesthesia for Thoracic Surgery will serve as an updated comprehensive review covering not only the recent advances, but also topics that haven't been covered in previously published texts: extracorporeal ventilatory support, new advances in chest imaging modalities, lung isolation with a difficult airway, pulmonary thrombo-endarterectomy, and chronic post-thoracotomy pain. Additionally, the book features clinical case discussions at the end of each clinical chapter as well as tables comprising detailed anesthetic management.
pt. 1. Preoperative evaluation -- pt. 2. Thoracic anatomy, physiology, and pharmacology -- pt. 3. Diagnostic and therapeutic procedures of the trachea and airways -- pt. 4. Diagnostic and therapeutic procedures of the mediastinum -- pt. 5. Anesthetic management for intra-thoracic surgery -- pt. 6. Specific patient considerations -- pt. 7. Complex thoracic surgical procedures -- pt. 8. Anesthetic management of uncommon pulmonary procedures -- pt. 9. Anesthesia for surgical procedures for end-stage lung diseases -- pt. 10. Anesthesia for pediatric thoracic surgical procedures -- pt. 11. Trauma -- pt. 12. Post-operative management.
Electronic reproduction.
Keywords: Chest -- Surgery; Anesthesia; Electronic books